Functional and clinical relevance of novel mutations in a large cohort of patients with Cockayne syndrome. Issue 5 (23rd March 2018) - Calmels, Nadege; Botta, Elena; Jia, Nan; Fawcett, Heather; Nardo, Tiziana; Nakazawa, Yuka; Lanzafame, Manuela; Moriwaki, Shinichi; Sugita, Katsuo; Kubota, Masaya; Obringer, Cathy; Spitz, Marie-Aude; et al.
Abstract : Background: Cockayne syndrome (CS) is a rare, autosomal recessive multisystem disorder characterised by prenatal or postnatal growth failure, progressive neurological dysfunction, ocular and skeletal abnormalities and premature ageing. About half of the patients with symptoms diagnostic for CS show cutaneous photosensitivity and an abnormal cellular response to UV light due to mutations in either the ERCC8 / CSA or ERCC6 / CSB gene. Studies performed thus far have failed to delineate clear genotype-phenotype relationships. We have carried out a four-centre clinical, molecular and cellular analysis of 124 patients with CS. Methods and results: We assigned 39 patients to the ERCC8/CSA and 85 to the ERCC6/CSB genes. Most of the genetic variants were truncations. The missense variants were distributed non-randomly with concentrations in relatively short regions of the respective proteins. Our analyses revealed several hotspots and founder mutations in ERCC6/CSB. Although no unequivocal genotype-phenotype relationships could be made, patients were more likely to have severe clinical features if the mutation was downstream of the PiggyBac insertion in intron 5 of ERCC6/CSB than if it was upstream. Also a higher proportion of severely affected patients was found with mutations in ERCC6/CSB than in ERCC8/CSA . Conclusion: By identifying >70 novel homozygous or compound heterozygous genetic variants in 124 patients with CS with different disease severity and ethnic backgrounds, we considerably broaden the CSA and CSB mutation spectrum responsible for CS. Besides providing information relevant for diagnosis of and genetic counselling for this devastating disorder, this study improves the definition of the puzzling genotype-phenotype relationships in patients with CS.